KL noir magic (Buku Fixi Sdn Bhd, 2021)
KL NOIR: MAGIC marks the resurrection of the notorious KL Noir series. The editor Deric Ee selects 20 original stories that bring you through the crimes and tribulations of life in Kuala Lumpur. There will be a bar hostess with a secret, a crisis in a minibus, well-dressed pontianaks, junkies discovering a new high, vampire slayers, and even an honest taxi driver. This time round, redemption may no longer be such an elusive thing...